Combinatorial Dynamics and an Elementary Proof of the Continuity of the Topological Entropy at ? =101, in the Milnor Thurston World - Labarca-Briones, R (2013)
In the present paper we deal with the Milnor-Thurston world and we present elementary proofs of some results by combining dynamics, combinatory, linear algebra and entropy. © Springer-Verlag Berlin Heidelberg 2013.